Uncertain Forms: Political Aspiration and Legal norm in the Peruvian Neoliberal State - Poole, Deborah (2018)
The present article aims to explore the way in which collectivity and authority is perceived and understood in the context of a recently decentralized, neoliberal state. In this sense, the author utilizes the concept of postregulatory government to refer to forms of government, prevalent in Peru and Latin America, in which the enforcement and issuance of regulatory standards and norms is left up to non-state agencies and institutions.By providing examples of real scenarios of decision-making at the local and regional government levels in the Peruvian Andes. The author aims to show how three components: collectivity, politics, and law, have reconfigured themselves as elements characteristic of the new decentralized, Peruvian state.